2009
DOI: 10.1186/1476-9255-6-20
|View full text |Cite
|
Sign up to set email alerts
|

Protein Never in Mitosis Gene A Interacting-1 regulates calpain activity and the degradation of cyclooxygenase-2 in endothelial cells

Abstract: Background: The peptidyl-proline isomerase, Protein Never in Mitosis Gene A Interacting-1 (PIN1), regulates turnover of inducible nitric oxide synthase (iNOS) in murine aortic endothelial cells (MAEC) stimulated with E. coli endotoxin (LPS) and interferon-γ (IFN). Degradation of iNOS was reduced by a calpain inhibitor, suggesting that PIN1 may affect induction of other calpain-sensitive inflammatory proteins, such as cyclooxygenase (COX)-2, in MAEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As a result, Pin1 knockdown or pretreatment with juglone, i.e., a Pin1 specific inhibitor, could provide protective roles against PD ( Tang et al, 2017 ). Besides, Pin1 has been reported to play a regulated role in neuronal death during glutamate excitotoxicity and influx of calcium ( Liu et al, 2009 ; Baik et al, 2015 ). Our study also found that both mRNA and protein levels of Pin1 were increased after glutamate treatment, which were consistent with others reports that Pin1 can be regulated transcriptionally and translationally ( Lu and Hunter, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, Pin1 knockdown or pretreatment with juglone, i.e., a Pin1 specific inhibitor, could provide protective roles against PD ( Tang et al, 2017 ). Besides, Pin1 has been reported to play a regulated role in neuronal death during glutamate excitotoxicity and influx of calcium ( Liu et al, 2009 ; Baik et al, 2015 ). Our study also found that both mRNA and protein levels of Pin1 were increased after glutamate treatment, which were consistent with others reports that Pin1 can be regulated transcriptionally and translationally ( Lu and Hunter, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that Pin1 plays a regulatory role in neuronal death induced by calpain during glutamate excitotoxicity ( Liu et al, 2009 ; Baik et al, 2015 ). Little is known about the relationship between Pin1 and calpain ( Galas et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro inhibition of PIN1 by juglone and PIN1 small-interfering RNA (siRNA) blocked ultraviolet A radiation-stimulated COX-2 expression and PGE 2 production in mouse epidermal cells (Quyen et al 2013) and decreased COX-2 expression in primary cultured chondrocytes from RA patients (Jeong HG et al 2009). However, PIN1 knockdown in endothelial cells increased COX-2 induction and PGE 2 production by LPS/interferon (Liu et al 2009). In contrast, PIN1 overexpression by a PIN1 adenovirus (Ad-PIN1) attenuated carbon tetrachloride-induced acute liver injury in mice by modulating apoptotic signals and increasing NF-κB activity (Risal et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Calpain/cathepsin protease inhibitors suppressed cleavage of COX-2 in human synovial fibroblasts [ 55 ]. Calpain inhibitor PD150606 dose-dependently increased lipopolysaccharide-induced COX-2 in murine aortic endothelial cells (MAEC), which was dose-dependently degraded by porcine μ-calpain [ 56 ].…”
Section: Calpains-induced Ed In Diabetesmentioning
confidence: 99%